Anthropometric data of selected Filipinos in Metro Manila for residential seat design a pilot study - Vergara, Avigail Asuncion (2001)
Chairs and sofa sold i the local market are not 'fit' for Filipinos. The absence of Filipino anthropometric data for furniture design force design professionals and furniture-makers to use the only available and accessible material - the American standards. The Caucasian body is larger than the Asian, specifically the Filipino. Adapting western sizes with the smaller Filipino as end-user results to designs that induce physical discomforts. This study is the first of its kind in the Philippines which was focused on anthropometric measurements for seat design such as the general-purpose chair, the sofa and the easy chair. This study introduced a system of deriving seat dimensions from body measurements based on ergonomic principles. Likewise, the study presented the partial anthropometric data in a format accepted by design practitioners. This cross-sectional research employed an anthropometric survey of 200 sample adult individuals composed of 100 males and 100 females in Metro Manila. Two-stage sampling was used to identify the barangay and the number of household members are in the age range of 18 to 60 years for females and 19 to 60 for males who are in their ideal growth status. Based from the study, changes in the standard seat dimesions are: 1) the wider the seat width of 480 mm from the standard of 400 mm; 2) the lower the seat height of 370 mm for general-purpose chairs and 350 mm for easy chairs from a range between 400 mm and 450 mm and 3) the lower armrest height of 150 mm from 180 mm up to 230 mm. Moreover, an innovation is introduced in the design of the backrest with a protrusion in the lumbar of 15 mm thick plotted in an arc of 115 mm up to 300 mm high taken from the seat.
Thesis (M. Interior Design)--University of the Philippines Diliman.
UARD-12142t, UARD-12143t Research project funded by University through the Office of the Vice-Chancellor for Research and Development (OVCRD).
Keywords: Seating (Furniture) -- Philippines -- Design; Interior decoration -- Human factor -- Philippines